Earthscan reader in rural-urban linkages - Tacoli, Cecilia (ed.) (London, 2006)
With accelerating urbanization and growing inter-dependence of rural and urban dwellers on the markets and resources they each offer, rural urban linkages have become a very important focus in recent years for research and policy relating to local and national economic development, poverty reduction and governance. The emergence of new livelihoods based on diversified income sources and mobility reflects profound social, cultural and economic transformations, and new forms of resource allocation and use. This volume collects the key contributions in the field, covering the conceptual background, the key issues and the current debates, locating different approaches in their wider intellectual and historical contexts. It also includes important recent empirical work from all the relevant geographical regions that that will be the basis for future thinking. Fifteen papers are clearly organized around the principal themes and accompanied by a valuable editorial introduction clearly setting out the issues, the arguments and the evidence.
Keywords: Rural-Urban linkage